A fully automated cell segmentation and morphometric parameter system for quantifying corneal endothelial cell morphology. (July 2018) - Al-Fahdawi, Shumoos; Qahwaji, Rami; Al-Waisy, Alaa S.; Ipson, Stanley; Ferdousi, Maryam; Malik, Rayaz A.; Brahma, Arun
Highlights: A fully automated and real-time cell segmentation and morphometric parameter system for quantifying corneal endothelial cell morphology is developed, termed the Corneal Endothelium Analysis System (CEAS). The CEAS system underpins the expertise of ophthalmologists. It is able to accurately detect the boundaries of the endothelial cells for the early diagnosis of corneal pathology and determining the health status of corneas for transplantation (Keratoplasty). A number of useful clinical features that can be used to save a useful amount of clinician time in the process. A clinically helpful diagnostic system for busy clinic and patient care. Abstract: Background and Objective: Corneal endothelial cell abnormalities may be associated with a number of corneal and systemic diseases. Damage to the endothelial cells can significantly affect corneal transparency by altering hydration of the corneal stroma, which can lead to irreversible endothelial cell pathology requiring corneal transplantation. To date, quantitative analysis of endothelial cell abnormalities has been manually performed by ophthalmologists using time consuming and highly subjective semi-automatic tools, which require an operator interaction. We developed and applied a fully-automated and real-time system, termed the Corneal Endothelium Analysis System (CEAS) for the segmentation and computation of endothelial cells in images of the human cornea obtained by in vivo corneal confocal microscopy. Methods: First, a Fast Fourier Transform (FFT) Band-pass filter is applied to reduce noise and enhance the image quality to make the cells more visible. Secondly, endothelial cell boundaries are detected using watershed transformations and Voronoi tessellations to accurately quantify the morphological parameters of the human corneal endothelial cells. The performance of the automated segmentation system was tested against manually traced ground-truth images based on a database consisting of 40 corneal confocal endothelial cell images in terms of segmentation accuracy and obtained clinical features. In addition, the robustness and efficiency of the proposed CEAS system were compared with manually obtained cell densities using a separate database of 40 images from controls ( n = 11), obese subjects ( n = 16) and patients with diabetes ( n = 13). Results: The Pearson correlation coefficient between automated and manual endothelial cell densities is 0.9 ( p < 0.0001) and a Bland–Altman plot shows that 95% of the data are between the 2SD agreement lines. Conclusions: We demonstrate the effectiveness and robustness of the CEAS system, and the possibility of utilizing it in a real world clinical setting to enable rapid diagnosis and for patient follow-up, with an execution time of only 6 seconds per image.